The last heir to blackwood library eaudiobook - Fox, Hester (Harlequin Audio, 2023)
"Weaves a spell of darkness that's mysterious and magical, and binds it with a knot of deathless love." — New York Times bestselling author Susanna Kearsley on A Lullaby for Witches In post – World War I England, a young woman inherits a mysterious library and must untangle its powerful secrets ... With the stroke of a pen, twenty-three-year-old Ivy Radcliffe becomes Lady Hayworth, owner of a sprawling estate on the Yorkshire moors. Ivy has never heard of Blackwood Abbey, or of the ancient bloodline from which she's descended. With nothing to keep her in London since losing her brother in the Great War, she warily makes her way to her new home. The abbey is foreboding, the servants reserved and suspicious. But there is a treasure waiting behind locked doors: a magnificent library. Despite cryptic warnings from the staff, Ivy feels irresistibly drawn to its dusty shelves, where familiar works mingle with strange, esoteric texts. And she senses something else in the library too, a presence that seems to have a will of its own. Rumors swirl in the village about the abbey's previous owners, about ghosts and curses, and an enigmatic manuscript at the center of it all. And as events grow more sinister, it will be up to Ivy to uncover the library's mysteries in order to reclaim her own story—before it vanishes forever. Lush, atmospheric and transporting, The Last Heir to Blackwood Library is a skillful reflection on memory and female agency, and a love letter to books from a writer at the height of her power. Delve into the magical power of flowers in Hester Fox's captivating new novel, THE BOOK OF THORNS, where long-lost sisters reunite on opposite sides of the Napoleonic Wars and must uncover the secrets of their mother's disappearance and their mystical powers... Look for these other gothic mysteries from Hester Fox: The Witch of Willow Hall The Widow of Pale Harbor The Orphan of Cemetery Hill A Lullaby for Witches